PENGEMBANGAN MEDIA E-BOOKLET INTERAKTIF MENGENAI PENCEGAHAN DIABETES MELITUS 2 PADA REMAJA - Ria Raihan, Zahra; Rizqi, M Aris (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Diabetes mellitus in West Java reached 644,704 people. Based on data in West Bandung Regency, it was found that people with type 2 diabetes mellitus reached 19,675 people, this was due to a lack of information through educational media. Therefore, interactive e-booklet media is needed to increase teenagers' knowledge and make it easier to provide health education in the era of digitalization. Goal: Produce interactive e-booklet media. Methodology: Using the ADDIE model includes qualitative research with a sample of 5 teenagers selected based on purposive sampling techniques and data collection was carried out using in-depth interviews. Quantitative research was carried out on 1 material expert, 1 media expert and 72 teenagers selected based on a purposive sampling technique carried out using data collection methods, namely a media feasibility test questionnaire and data analysis using the feasibility percentage formula. Results: Qualitative research at the Analyze and Design stage was carried out by in-depth interviews with 5 teenagers regarding the contents of the E-Booklet. Quantitative research at the Development, Implementation and Evaluate stages shows that the feasibility test results from material experts are 100%, media experts are 100% and teenagers are 86%, meaning the media is